The Influence of Transformational Leadership on Work Motivation and Work Productivity - Tarya WItarsa; Siti Musliha; Winur Asri (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
AbstractTransformational leadership is one of the leadership models capable of positively influencing employee motivation and work productivity. This study aims to analyze the influence of transformational leadership on work motivation and productivity within organizations. The method used in this research is a qualitative descriptive method with a literature study approach. Data were collected from scientific sources such as books, journals, and previous research relevant to the study topic. The results indicate that transformational leadership has a significant relationship with increased employee motivation through inspiration, individual consideration, and innovation encouragement. Furthermore, transformational leadership also improves work productivity by creating an effective, harmonious, and participatory work culture. Therefore, the implementation of transformational leadership in organizations becomes an important strategy in improving the quality of human resources and achieving organizational goals.Keywords: Transformational Leadership, Work Motivation, Work Productivity, Organization, Human Resource Management.